Dioxins, Furans and PCBs in recycled water for indirect potable reuse - Rodriguez, C.; Cook, A.; Devine, B.; Van Buynder, P.; Lugg, R.; Linge, Kathryn; Weinstein, P. (Molecular Diversity Preservation International (MDPI), 2008)
An assessment of potential health impacts of dioxin and dioxin-like compounds in recycled water for indirect potable reuse was conducted. Toxic equivalency factors (TEFs) for 2,3,7,8-substituted polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDFs) and dioxin-like polychlorinated biphenyls (PCBs) congeners have been developed by the World Health Organization to simplify the risk assessment of complex mixtures. Samples of secondary treated wastewater in Perth, Australia were examined pre-and post-tertiary treatment in one full-scale and one pilot water reclamation plant. Risk quotients (RQs) were estimated by expressing the middle-bound toxic equivalent (TEQ) and the upper-bound TEQ concentration in each sampling point as a function of the estimated health target value. The results indicate that reverse osmosis (RO) is able to reduce the concentration of PCDD, PCDF and dioxin-like PCBs and producewater of high quality (RQ after RO=0.15). No increased human health risk from dioxin and dioxin-like compounds is anticipated if highly treated recycled water is used to augment drinking water supplies in Perth. Recommendations for a verification monitoring program are offered.